Naringin Attenuates Aluminum Induced Cognitive Deficits in Rats (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The exposure of aluminum for longer period in brain can lead to impaired cognition and behavioral changes. The present study was aimed to investigate the aluminum induced cognitive deficits and possible protective outcomes of naringin. Materials and Methods: Aluminum chloride in a dose of 100 mg/kg i.p was employed for 60 days to induce cognitive deficits in Westar rats. The animals were divided into groups each group contain six animals, as normal, aluminum treated, naringin treated (25, 50, 100 mg/kg). These animals were used to estimate behavioral characters such as Open field, eight arm radial maze, Morris water maze and Rota-rod tests and also used to assess the biochemical parameters such as acetylcholine esterase activity, malondialdehyde, superoxide dismutase and catalase. Results: Aluminum intoxicated rats showed significantly reduced exploratory and spontaneous locomotors activities in open field test and significant impairment in working and learning memory assessed by Morris water maze and radial arm maze tests. It also significantly increased acetylcholine esterase activity and malondialdehyde. The superoxide dismutase and catalase were also decreased significantly. Naringin was given (25, 50 and 100 mg/kg PO) to the aluminum intoxicated rats for a period of 30 days. The naringin treatment has shown significant improvements in spontaneous locomotors and exploratory activities and memory performance tasks of rats. Conclusion: The oxidative stress (reduced lipid peroxidation, restored reduced superoxide dismutase and catalase) and acetylcholine esterase activity were significantly decreased in the naringin group. Thus, these findings supported that naringin has showed potential neuroprotection against aluminum induced oxidative stress and cognitive deficit.
Keywords: Acetylcholine esterase; Aluminum; Alzheimer; Cognitive impairment; Oxidative stress; Naringin